1988
DOI: 10.1126/science.2829356
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenesis in Response to PDGF and Bombesin Abolished by Microinjection of Antibody to PIP 2

Abstract: The turnover of phosphatidylinositol 4,5-bisphosphate (PIP2) is believed to constitute a crucial step in the signaling pathways for stimulation of cells by a variety of bioactive substances, including mitogens, but decisive evidence for the idea has not been obtained. In the present study, a monoclonal antibody to PIP2 was microinjected into the cytoplasm of NIH 3T3 cells before or after exposure to mitogens. The antibody completely abolished nuclear labeling with [3H]thymidine induced by platelet-derived grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 34 publications
3
65
1
Order By: Relevance
“…This characteristic of ARDs is comparable to that of antibodies, in that antibodies can be generated against lipids, including PI(4,5)P 2 (ref. 52). Therefore, the highly diverse characteristics of ARDs may support their ability to recognize a variety of molecules, including lipids.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of ARDs is comparable to that of antibodies, in that antibodies can be generated against lipids, including PI(4,5)P 2 (ref. 52). Therefore, the highly diverse characteristics of ARDs may support their ability to recognize a variety of molecules, including lipids.…”
Section: Discussionmentioning
confidence: 99%
“…and immunostained with antion. Monoclonal antibody to PtdIns(4,5)P2 was prepared as described before [24,25].…”
Section: Preparation Of Antibodies Polyclonal Antibodies To His-mentioning
confidence: 99%
“…[ 3 H]PtdIns(4,5)P 2 (7.6 Ci/mmol) and proteins using a monoclonal antibody to PtdIns(4,5)P 2 , which is [γ-32 P]ATP were purchased from Du Pont New England Nuclear very specific and does not recognize other phospholipids such and Amersham, respectively. Drosophila embryo nuclear extract as PtdIns and PtdIns4P [24,25]. Using this antibody, we have in vitro transcription system was from Promega.…”
mentioning
confidence: 99%
“…Available data have largely suggested that PDGF receptor mediates inositol phosphate generation through mechanisms independent of toxinsensitive G proteins (23)(24)(25)(26)(27)(28)(29). At least five distinct proteins with PLC activity have been identified and cloned, differing in tissue distribution, substrate specificity, and Ca2+ and pH dependence (30).…”
mentioning
confidence: 99%